Buds of Jewish-Christian Dialogue in a German Milieu: Caspar Amman (c. 1450-c. 1524) and His Hebrew Correspondence - Ron, Natan (Renaissance and reformation, 2024)
This year, 2024, is the 500th anniversary of Caspar Amman's passing. The German priest and Hebraist kept records of nineteen letters in Hebrew. The letters portray not only a picture of scholarly early modern Jewish-Christian collaboration, as Eric Zimmer has shown, but also an attempt by at least one Jewish rabbi to initiate a dialogue with the German priest. The exceptional letter, addressed to Caspar Amman by Rabbi Moshe Elchanan Bacharach from Swabia, was hitherto not translated into English and barely referenced in the literature. This and additional letters, sixteen in total, are published here for the first time in English (in the appendix). The epistolary corpus reflects mutual respect and appreciation, a shared love for the Hebrew language and the Hebrew book, and the use, by Hebraists, of the title "rabbi" to mark respect and appreciation. Given Gershom Scholem’s denial of any historic German-Jewish dialogue - or, alternatively, irrespective of it - these buds of a Christian-Jewish dialogue appear like rays of light piercing the darkness. Still, they could not withstand the spirit of the time.